Expanded Spectrum of Antiretroviral-Selected Mutations in Human Immunodeficiency Virus Type 2 - Tzou, Philip L.; Descamps, Diáne; Rhee, Soo-Yon; Raugi, Dana N; Charpentier, Charlotte; Taveira, Nuno; Smith, Robert A; Soriano, Vicente; Mendoza, Carmen de; Holmes, Susan; Gottlieb, Geoffrey S.; Shafer, Robert W. (Journal of Infectious Diseases, 2020)
Background: HIV-1 and HIV-2 differ in their antiretroviral (ARV) susceptibilities and drug resistance mutations (DRMs). Methods: We analyzed published HIV-2 pol sequences to identify HIV-2 treatment-selected mutations (TSMs). Mutation prevalences were determined by HIV-2 group and ARV status. Nonpolymorphic mutations were those in <1% of ARV-naive persons. TSMs were those associated with ARV therapy after multiple comparisons adjustment. Results: We analyzed protease (PR) sequences from 483 PR inhibitor (PI)-naive and 232 PI-treated persons; RT sequences from 333 nucleoside RT inhibitor (NRTI)-naive and 252 NRTI-treated persons; and integrase (IN) sequences from 236 IN inhibitor (INSTI)-naive and 60 INSTI-treated persons. In PR, 12 nonpolymorphic TSMs occurred in ≥11 persons: V33I, K45R, V47A, I50V, I54M, T56V, V62A, A73G, I82F, I84V, F85L, L90M. In RT, 9 nonpolymorphic TSMs occurred in ≥10 persons: K40R, A62V, K70R, Y115F, Q151M, M184VI, S215Y. In IN, 11 nonpolymorphic TSMs occurred in ≥4 persons: Q91R, E92AQ, T97A, G140S, Y143G, Q148R, A153G, N155H, H156R, R231 5-amino acid insertions. Nine of 32 nonpolymorphic TSMs were previously unreported. Conclusions: This meta-analysis confirmed the ARV association of previously reported HIV-2 DRMs and identified novel TSMs. Genotypic and phenotypic studies of HIV-2 TSMs will improve approaches to predicting HIV-2 ARV susceptibility and treating HIV-2-infected persons.
Keywords: mutation; drug resistance; hiv-2; integrase inhibitors; anti-retroviral agents; Scopus; JCR